RESEARCH OF ROBOT - HUMANOID CONTROL METHODS USING HUMAN BODY MOTION RECOGNITION TOOLS - Sakalys, Paulius; Savulioniene, Loreta; Savulionis, Dainius (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2022)
The aim of the research is to investigate and evaluate the repetition indices of the displacements of the robot‘s kinematic nodes, using the means of identification human body movements, using a real robotic system. The article presents an analysis of human body motion recognition tools, identifies typical application criteria that meet the requirements of robotic systems control, describes the developed physical research stand "Robot - humanoid": the robotic system is identified with the human body with two of nine-kinematic degrees of freedom hands and a two degree of freedom robotic mechanism replacing the head on which the environmental video surveillance equipment is mounted. The publication presents systematized experimental data and suggestions for the integration of research results into the process of students' practical - applied teaching in a contact or distance way.